IMPLEMENTASI PENDIDIKAN KARAKTER OLEH KOMUNITAS MUSLIMAT DALAM MENANGGANI KENAKALAN REMAJA DI KABUPATEN BENGKULU TENGAH - Supardi Mursalin; Hamdan Hamdan (Muróbbî: Jurnal Ilmu Pendidikan, 2022)
This study describes the implementation of character education in the Muslimat community in handling juvenile delinquency holistically. Juvenile delinquency is a problem that often arises in society. When a teenager fails to find his identity, he will experience an identity crisis, often leading to deviant behavior. This field research uses interview and documentation techniques in the data collection process. While the analysis technique used is descriptive. After conducting an in-depth study, it was concluded that character education has a very significant role in the Muslimat Community in dealing with juvenile delinquency in Central Bengkulu Regency. The form of character education implemented by Kumintas Muslimat is as an ustadazh or educator who gives attention and affection, sets a good example, and instills discipline, as a group guide by providing religious education and encouraging teenagers to fill their free time with positive activities. Meanwhile, the obstacles that arise when implementing character education are the lack of public understanding of Muslim organizations, which results in a lack of appreciation for these institutions, obstacles from families who do not care about children/family members, and the lack of role of educational institutions to motivate teenagers/students. to maintain positive values ??in their social life.